2018
DOI: 10.1093/dote/doy048
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of robot-assisted Ivor–Lewis esophagectomy: 61 consecutive cases from a single Chinese institution

Abstract: This study aims to report the technical details and preliminary outcomes of robot-assisted Ivor-Lewis esophagectomy (RAILE) using two different types of intrathoracic anastomosis from a single institution in China. From May 2015 to October 2017, 61 patients diagnosed with mid-lower esophageal cancer were treated with RAILE. The RAILE procedure was performed in two stages. The first 35 patients underwent circular end-to-end stapled intrathoracic anastomosis (stapled group), and the remaining 26 patients had a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…There were also several reports on robot hand-sewn intrathoracic EGA. But they only contained a small number of surgical cases and the technique of robot hand-sewn intrathoracic EGA was still under exploration without wide acceptation (14)(15)(16)(17)(18)(19).…”
Section: Original Articlementioning
confidence: 99%
“…There were also several reports on robot hand-sewn intrathoracic EGA. But they only contained a small number of surgical cases and the technique of robot hand-sewn intrathoracic EGA was still under exploration without wide acceptation (14)(15)(16)(17)(18)(19).…”
Section: Original Articlementioning
confidence: 99%
“…[28][29][30] Table 2 shows case series studies of Ivor Lewis RAMIE including more than 10 cases. [31][32][33][34][35][36][37][38][39][40][41][42] Only four studies reported recurrent nerve injury with the average rate of 4.2%. 31,33,37,39 On the other hand, recurrent nerve injury rates in the case series of McKeown RAMIE were reported to be 2.9%-29% with the average rate of 15.9%.…”
Section: Ivor Le Wis R Amiementioning
confidence: 99%
“…Morbidity was minimal, 30-day mortality was 0%, and they ultimately concluded that RAILE was a safe and oncologically sound procedure [62] . Since that time, many more have reported on their experience performing robotic IL esophagectomy [74][75][76][77][78][79][80][81] and more recently, Nora et al [82] reviewed outcomes of RAILE. When completed by an experienced surgeon, RAILE has comparable times to esophagectomies performed via minimally invasive approaches [28,83] .…”
Section: Outcomes Of Robotic Esophagectomymentioning
confidence: 99%